2001
DOI: 10.1099/00207713-51-4-1373
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium microaerophilum sp. nov., a microaerophilic bacterium isolated from olive mill wastewater.

Abstract: A new Gram-positive, facultative anaerobic, microaerophilic bacterium, designated strain M5 T , was isolated from a decantation reservoir of olive mill wastewater. The cells were rod-shaped, non-motile, non-spore-forming and catalase-negative. Growth occurred at pH ranging from 45 to 95, with optimum growth at 70. The optimum temperature for growth was around 30 SC. Although growth occurred under anaerobic and aerobic conditions, the optimum O 2 concentration for growth was determined as 5 % in the gas phase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…In the last two decades six new species were isolated: P. cyclohexanicum was obtained from spoiled orange juice [10]; P. microaerophilum was isolated from olive mill wastewater [11]; P.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades six new species were isolated: P. cyclohexanicum was obtained from spoiled orange juice [10]; P. microaerophilum was isolated from olive mill wastewater [11]; P.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic studies have shown that P. jensenii and P. thoenii are more closely related than other dairy propionibacteria (4,13). The strains harboring the pctA and pamA genes were obtained from different environments in Europe, the United States, and South Africa, indicating that the ability to produce these antimicrobial compounds is widely distributed in the two species.…”
Section: Discussionmentioning
confidence: 99%
“…According to the sequence of 16S rRNA, new Propionibacterium species isolated from other biotopes have exhibited similarity to the dairy propionibacteria. Propionibacterium cyclohexanicum (Kusano, Yamada, Niwa, & Yamasato, 1997) was shown to be phylogenetically related to P. freudenreichii, whereas Propionibacterium microaerophilum (Koussemon et al, 2001) was shown to be related to P. acidipropionici.…”
Section: Introductionmentioning
confidence: 96%